Protection de la ressource en eau du bassin de l’Auxerrois et transformation des pratiques agricoles - Simon Calla; Sébastien Dassé; Lou Lécuyer; Juliette Young (VertigO)
With nitrate levels exceeding the thresholds defined by the European "nitrates" Directive, and the presence of pesticide residues used by the sector's agricultural activities, the water in the catchment areas of the Auxerrois has been the subject of concern for some thirty years. Thus, at the end of the 1990s, the representatives of the public authorities chose to set up a preventive approach involving the transformation of agricultural practices. Our article analyzes how the collective assumption of responsibility for this situation contributes to the configuration of relations between representatives of public authorities, farmers and environmentalists. We show that the link with local elected officials and the creation of an association promoting soil conservation agriculture initially enabled some farmers to define the solutions to be adopted in this approach. The study also shows that the observation of pesticide residues in water intended for human consumption from the mid-2000s onwards produced a new framing of the situation. It is then that an opposition between the supporters of soil conservation agriculture and those of organic agriculture emerges.